2015
DOI: 10.1186/s13048-015-0201-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of reference intervals of serum levels of human epididymis protein 4 (HE4) in Chinese women

Abstract: BackgroundTo determine reference intervals for serum levels of human epididymis protein 4 (HE4) in Chinese women.MethodsIn this multicenter (n = 9) study, 618 healthy women, 767 patients with non-malignant diseases, and 951 patients with malignant tumors were enrolled. Serum levels of HE4 were measured in all patients using electrochemiluminescence immunoassays. The influence of age, menopause, malignancy status and other characteristics on the levels of HE4 was evaluated using univariate and multivariate anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Recently, human epididymis secretary protein 4 (HE4) emerged as 1 of the most promising biomarker for the diagnosis of epithelial ovarian cancer (EOC). 8 It is demonstrated to be overexpressed in ovarian carcinomas but not in the normal ovary tissue. Its SN was similar to CA125, but an increased diagnostic SP.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, human epididymis secretary protein 4 (HE4) emerged as 1 of the most promising biomarker for the diagnosis of epithelial ovarian cancer (EOC). 8 It is demonstrated to be overexpressed in ovarian carcinomas but not in the normal ovary tissue. Its SN was similar to CA125, but an increased diagnostic SP.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that HE4 levels may not be related to menopausal status, but age is an important factor that caused the most notable increase, especially for women after age 79 years. Recently, Tian et al reported a multicenter study in nine Chinese hospitals that enrolled 618 healthy women, 767 patients with nonmalignant disease and 951 patients with malignant disease [37]. Multivariate analysis showed that menopause but not age was an independent factor involved in serum HE4 levels.…”
Section: He4 Levels In Female Reproductive Cyclesmentioning
confidence: 99%
“…Another study, published in 2015, attempted to define HE4 reference ranges within a Chinese study population and found the norm to be between 29.30 pmol/l and 68.79 pmol/l for premenopausal women and between 35.96 pmol/l and 114.43 pmol/l for postmenopausal women [9].…”
Section: Discussionmentioning
confidence: 99%